Pendampingan Operasional Toko Online “BUMDes Mart Mulyoagung - Hariyani, Happy Febrina; Nuraini, Ida (JOURNAL OF ECONOMIC AND SOCIAL EMPOWERMENT, 2024)
The purpose of mentoring activities for service partners, namely Bumdes Mart Mulyoagung in Mulyoagung village, Dau sub-district, Malang district, is to develop a shopping business unit by opening a shop on the Shopee marketplace. By opening a shop on the marketplace, it is hoped that it can increase store sales, which so far have experienced problems with delays in the delivery of goods and no increase in sales due to limited consumers, namely only those with shop business WhatsApp numbers. Village community products will also be able to reach a wider range of consumers by opening shops on the marketplace. Activities are carried out in stages starting from the preparation, implementation, and evaluation stages. The results of the activity were the formation of the Bumdes Mart Mulyoagung online store on the Shopee marketplace as well as online sales transactions. It is hoped that increased sales through the marketplace will increase shop profits so that they can be used for store operational costs, and the excess can provide input for Village Original Income.